KENDALA DAN HAMBATAN PEMENUHAN KESESUAIAN KEGIATAN PEMANFAATAN RUANG (KKPR) DALAM SERTIPIKASI TANAH MILIK PEMERINTAH KOTA MALANG - Alodia Salsabila; Mohammad Hamidi Masykur; R. Imam Rahmat Sjafi'i (Universitas KH. Abdul Chalim Mojokerto, 2025)
In principle, it can be seen that the granting of land rights is based on the allocation of space in accordance with the spatial plan. In its development, there are still legal phenomena in the form of violations of spatial planning. The law explicitly stipulates that the granting of land rights must be based on the use of space, including in the certification process of Regional Property as an asset security activity. Currently, the Malang City Government is actively implementing a BMD certification program in the form of land in the Malang City Area. The certification of regional government asset land is certainly not carried out without obstacles. Normatively based on the provisions of Article 115 letter c of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 18 of 2021 concerning Procedures for Determining Management Rights and Land Rights, the Malang City Government is required to attach the requirements for the Conformity of Spatial Utilization Activities document so that the Regional Government in the process of implementing the certification of Regional Property does not carry out potential activities that can result in violations of spatial planning. However, based on the survey that the author has conducted, it is known that it seems that the fulfillment of the KKPR document cannot be carried out following the legal mandate. Moreover, it is known that many of the assets of the Malang city government are settlements utilized by the community. Therefore, further study is needed regarding the obstacles and barriers to fulfilling the suitability of spatial utilization activities (KKPR) in the certification of land owned by the Malang city government.